Synthesis of CdIn2S4 Microsphere and Its Photocatalytic Activity for Azo Dye Degradation - Jianhui Huang; Wei Lin; Jianqin Chen (The Scientific World Journal)
CdIn2S4 was prepared by ultrasonic spray pyrolysis. The prepared CdIn2S4 was characterized by X-ray diffraction (XRD), field emission scanning electron microscopy (FSEM), transmission electron microscopy (TEM), UV-visible diffuse reflectance spectroscopy (UV-Vis DRS), and N2-sorption techniques. Aqueous photocatalytic activity was evaluated by the decomposition of methyl orange under visible light irradiation. The results indicate that the prepared CdIn2S4 has spherical morphology with mesoporous structure which can efficiently degrade methyl orange in water. The sample prepared at 500°C exhibits the optimized photocatalytic activity.